AMMIAKNI SINTEZ QILISH MAVZUSINI O‘QITISHDA AXBOROT TEXNOLOGIYALARIDAN FOYDALANISH METODIKASI - Kurbanbaeva, A.J.; Genjemuratova, G.P. (SCIENCE and SOCIETY, 2017)
The article deals with the study of ways of teaching on the topic of the synthesis of amiac in the educational process, and using modern pedagogical and information technologies. The authors of the article worked out the techniques of critical thinking, that help to improve activization at the lesson.